2001
DOI: 10.1002/1616-5195(20010601)1:4<126::aid-mabi126>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

New MethacryloxyN-Vinyl-2-pyrrolidinone- and Lactone-Based Macromers

Abstract: Monomer conversion (0) and degree of polymerization ( 6 ) of d-VL macromer as a function of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The synthesis of HEMA‐Im (Scheme ) was performed as already reported 9,11. Briefly, HEMA was treated with CDI in alcohol‐free chloroform at room temperature and without added catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of HEMA‐Im (Scheme ) was performed as already reported 9,11. Briefly, HEMA was treated with CDI in alcohol‐free chloroform at room temperature and without added catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the preparation of end‐hydroxylated PVP oligomers previously mentioned, PVP oligomers bearing at one terminus ester residues were prepared by radical polymerization of NVP in the presence of aliphatic esters acting in the meantime as solvents and chain transfer agents. The chain transfer involved one hydrogen atom α to the ester function . Compared with ATRP or RAFT, this synthetic method gave end‐functionalized oligomers with broader molecular weight distribution, but had the merit of being very simple and easily scaled‐up.…”
Section: Introductionmentioning
confidence: 99%
“…The initiator was prepared by an efficient one-step process (Scheme 1). At first, 2-hydroxyethylmethacrylate (HEMA), which has been used as a coinitiator in some studies, 14,16,[23][24][25][26] was used as a reagent, but we found that the chemical modification reaction was impossible to control, and the characterizations proven there were some transesterification reactions. When 2-allyloxyethanol (AEOH) was used as alcohol, the initiator was successfully prepared without side reactions.…”
Section: Introductionmentioning
confidence: 99%